Model values for goniometric parameters of 6–8 year-old children’s body pairs in boundary moments of their walking phase - Kholodov, Serhii (Journal of Education, Health and Sport, 2017)
Topicality. The heart of a holistic and comprehensive research of human physical status is the studies of its morphological and functional parameters. Goniometry of the human body is one of the aspects of dynamic anthropometry. Currently, due to the development of modern technologies, electric goniometric systems have been recently developed. The task of the research is to develop model values for goniometric parameters of 6–8 year-old children’s body pairs in the boundary moments of their walking phases. Research methods include analysis of scientific and methodical resources as well as documentary materials, video-metrics, BioVideo application package, methods of mathematical statistics. Research results. The BioVideo application package allows obtaining biomechanical characteristics of both individual bio-links and the whole human body. BioVideo application software includes four modules. Module for designing human musculoskeletal system models was used, in particular a 14-segment branched bio-kinematic chain as a model of the musculoskeletal system, the link coordinates of which by geometric characteristics correspond to the coordinates of the human body bio-links position in the space, and reference points correspond to the coordinates of the main joints). In the course of work model values of goniometric indicators of 6–8 year-old children’s body pairs in boundary moments of walking phases have been developed. Conclusion. The method of goniometry has been developed by scientists and specialists in the field of control of human motor function. Analysis of a huge scope of scientific resources allows us to state choosing control influences, developing prognostic models for assessing children's motility in order to program optimal modes for exercise and substantiate objective ergonomic standards for designing samples of various elements of the technogenic environment around modern human.